KEBERTERIMAAN WISATAWAN DAN PEDAGANG TERHADAP METODE PENGELOLAAN LIMBAH BERKELANJUTAN DI OBYEK WISATA BAHARI GUNUNGKIDUL, YOGYAKARTA - Muhammad Zumar Rahafuna (Jurnal Pariwisata Tawangmangu, 2026)
This study aims to analyze the level of acceptance of tourists and vendors towards the implementation of sustainable solid waste management in the Gunungkidul marine tourism area. The background of the study is the increasing tourism activity, which has resulted in high waste volumes and suboptimal sustainable management. The research method used was a qualitative descriptive approach supported by quantitative data through a survey of 270 tourists and in-depth interviews with 24 vendors. Data were analyzed using descriptive statistics and qualitative interpretation techniques within the Miles and Huberman framework. The results indicate that tourists generally have a high level of acceptance of sustainable waste management, particularly regarding environmental awareness and willingness to comply with technical regulations. However, there are doubts regarding implementation, particularly regarding additional costs. Meanwhile, vendors expressed openness to implementing a sustainable waste management system despite limited knowledge and experience. The conclusion of this study confirms that conceptual acceptance is strong, but an adaptive implementation strategy is needed for effective field implementation.